Exercise Improves Respiratory Function, Body Fluid and Nitric Oxide in Hemodialysis Patients - Neves, Rodrigo Vanerson Passos; Corrêa, Hugo Luca; Reis, Andrea Lucena; Andrade, Rosangela Vieira; Araújo, Thais Branquinho; Santos, Rafael Lavarini; Oliveira, Fernanda Félix Santos; Moraes Araújo, Guilherme Eduardo Barbosa; Marra, André Victor Gulyas; Baracho, Thaís Amaral; Martins, Taynah Oliveira; Barbosa, Jessica Mycaelle da Silva; Garcia, Mariana Neiva; Miller, Nicole Messenberg Guimarães; Deus, Lysleine Alves; Rosa, Thiago dos Santos (International Journal of Sports Medicine, 2024)
Emerging evidence suggests that resistance training (RT) can mitigate respiratory muscle weakness in hemodialysis (HD) patients. However, the underlying mechanisms responsible for these beneficial effects remain unclear. The purpose of this study was to assess the impact of periodized RT on respiratory muscle strength and its relationship with handgrip strength (HGS), fat-free mass (FFM), nitric oxide (NO), and interdialytic weight gain (IWG) in HD patients. Thirty-three patients were randomly assigned to two groups: control (CTL; n=18) and RT (n=15). The RT group did not perform any additional exercise training specific to the respiratory tract. Maximal inspiratory (MIP) and expiratory (MEP) pressures, peak expiratory flow (PEF), HGS, FFM, NO, and IWG were measured before and after the intervention period. Participants in the RT group engaged in a 24-week RT program, three times per week. RT resulted in significant improvements in MIP, MEP, PEF, as well as enhancements in HGS, FFM, NO, and IWG (p<0.05). Notably, inverse correlations were observed between MIP (r=−0.37, p=0.03) and PEF (r=−0.4, p=0.02) with IWG. Thus, the amelioration of HGS and FFM coincided with a reduction in respiratory muscle weakness among HD patients. Decreased IWG and increased circulating NO are plausible mechanisms contributing to these improvements.
Keywords: exercise; end-stage renal disease; respiratory performance; lung; endothelial dysfunction; edema